Breaking the Mould: Alternative approaches to monitoring and evaluation - and Dillon, Neil (ALNAP, 2019)
This paper looks at a range of M&E innovations that are designed specifically to provide input to ongoing iterative decision-making and learning at the project level. It identifies three key areas for potential innovation: 1) timing of M&E data provision; 2) flexibility of M&E frameworks to evolve with programme change; and 3) approaches to integrate diverse perspectives on project implementation in a meaningful way. It then looks at a collection of approaches currently being used in each of these three areas through a series of ‘practice examples’, considering the key lessons learned. Finally, the paper discusses the major opportunities and challenges for applying and scaling up the use of these approaches inside the humanitarian sector.